Australian student nurse's knowledge of and attitudes toward primary health care: A cross-sectional study. (January 2018) - Mackey, Sandra; Kwok, Cannas; Anderson, Judith; Hatcher, Deborah; Laver, Sharon; Dickson, Cathy; Stewart, Lyn
Abstract: Background: Nurses have a pivotal role in changing the focus of the health system toward a primary health care approach, yet little is known about the effectiveness of nursing students' educational preparation for this role. Objectives: The aim of the study was to investigate undergraduate Australian nursing students' knowledge of and attitudes toward the primary health care approach. Design: A cross-sectional, descriptive research design was applied. Setting: Two Australian universities, one with a rural base and one in the metropolitan area of Sydney, were involved. Both universities offer undergraduate and postgraduate nursing courses on multiple campuses. Participants: A convenience sample of 286 undergraduate nursing students, each of whom had completed a unit of study on PHC. All provided consent to participate in the study. Methods: Data was collected using the Primary Health Care Questionnaire via online survey platform SurveyMonkey for a period of three weeks in June 2015. Results: Total knowledge scores ranged from 19.68 to 95.78 with the mean knowledge score being 69.19. Total attitude scores ranged from 33.12 to 93.88 with a mean score of 70.45. Comparison of knowledge scores showed mean scores of students born in Australia were significantly higher than those of students who were born overseas ( p = 0.01), and mean scores of students enrolled in the metropolitan university were also significantly higher than mean scores of students' enrolled in the rural university ( p = 0.002). In terms of attitudes scores, mean scores of Australian-born students were significantly higher than those of students born overseas ( p = 0.001), and older students' mean attitude scores were shown to be significantly higher than younger students' ( p < 0.005). Conclusions: Student's age, country of origin and university location were shown to be significant influences on student's knowledge of and attitudes toward primary health care. Highlights: Nurses have a pivotal role in primary health care. Little is known about nursing students' knowledge of and attitudes toward primary health care. Demographic factors have influences on student's knowledge and attitudes toward primary health care.